The status quo and prospect of transfer and shift in patients receiving hemodialysis in ChinaThis project was supported by Health and Family Planning Commission of Chongqing Medical Research Project (No. 2016ZDXM008), the outstanding young nurses in Second Hospital Affiliated to Chongqing Medical University (No. 201707), and Hospital Research and Construction Project of Chinese Medical Doctor Association (No. 201522). - Zhang Tian; Gan Xiu-Ni; Tang Wei; Zou Min; Zhang Ying (Sciendo, 2019)
Hemodialysis is the main alternative therapy for patients with end-stage renal disease; most of the hemodialysis centers in China are not designed together with the inpatient ward. During the hospitalization period, hemodialysis patients often move back and forth between wards and hemodialysis rooms because of the treatment needed. Hemodialysis patients are a special group of hospitalized patients, most of them are elderly patients. The overall basic diseases of the patients vary very much, and the cause of the disease is complex. Moreover, the chronic inflammation progresses slowly, and immune function declines. Some of the patient are seriously ill or even hav organ failure. All these factors affect the patients in general. Therefore, the transfer safety of patients during hospitalization is facing great challenges. The researchers reviewed the status of transshipment research in Chinese hemodialysis patients and laid the foundation for the research and development of related handover tools and perfect handover mode in the future.